Nivolumab plus cabozantinib in metastatic renal cell carcinoma: real-world evidence from the international ARON-1 study - Bourlon, Maria T.; Galli, Luca; Grande, Enrique; Park, Se Hoon; Melichar, Bohuslav; Schieber, Timothy J.; Juan-Fita, Maria José; Ürün, Yüksel; Molina-Cerrillo, Javier; Alonso-Gordoa, Teresa; De Giorgi, Ugo; Kucharz, Jakub; et al. (Frontiers in Oncology, 2025)
IntroductionFour approved immune-based combinations for untreated metastatic renal carcinoma have demonstrated survival benefits. The ARON-1 study (NCT05287464) analyzed real-world data of patients with metastatic renal cell carcinoma receiving first-line immuno-oncology combinations. This sub-analysis is focused on the nivolumab plus cabozantinib effectiveness.MethodsWe conducted a retrospective study across 52 centers in 17 countries, including patients with metastatic renal carcinoma treated with first-line nivolumab plus cabozantinib, regardless of histologic characteristics, performance status, or risk by IMDC prognostic model. Patients with incomplete medical data were excluded. The primary objective of this sub-analysis of the ARON-1 study was to evaluate the real-world effectiveness and safety.ResultsA total of 333 patients were treated with nivolumab plus cabozantinib, clinical characteristics included ECOG performance status ≥2 20%, non-clear cell histology 16%, sarcomatoid de-differentiation 12%, and poor-risk by IMDC 28%. At a median follow-up of 15.9 months (95%CI 11.2-44.0), the median overall survival was not reached (40.0–NR), the probability of survival at 2 years was 75%, while median progression free survival was 33.7 months (95%CI 21.1-38.9). In the entire cohort, an objective response was observed in 58%, with 6% complete responses, and a median duration of response of 38.9 months (95%CI 33.7–NR). At multivariate analysis, adverse prognostic factors for overall survival included ECOG performance status ≥2, sarcomatoid de-differentiation, brain and bone metastases, and poor IMDC group. In the safety analysis, the incidence of grade 3 or higher toxicity was 37%, with hypertension and hand-foot syndrome being the most frequent adverse events.ConclusionThe findings in the present real-world study reaffirm the clinical benefits and safety of the nivolumab plus cabozantinib combination across all subgroups, including populations that are generally excluded from clinical trials for whom data is often missing. Poor performance status, sarcomatoid de-differentiation, bone or central nervous system metastases and IMDC poor risk group were confirmed as negative prognostic factors.